Effect of mobile phone usage on semen analysis in infertile men (Tikrit Journal of Pharmaceutical Sciences, 2023)
There has been scientific interest in the possible effects of continuous or pulsed exposure to microwave radiation as emitted by mobile phones. The use of mobile phones adversely affects the quality of semen. To determine the effect of mobile phone use on parameters of semen analysis in infertile men. Cross-Sectional study. Fertility, Infertility and IVF centre in Al – Batool Mosul Teaching Hospital for the period from 2009-2010. This study was conducted on 300 patients complaining of infertility after 2003, their mean age (29.87 ± 6.4) years. They were classified according to their active mobile phone use into group 1: 4 h / day; group 2: 3 h / day; group 3: 2 h / day; group 4: no use. Also they were classified according to the duration of use in years into group A: from 1 – 3 years; group B: from 4 – 6 years. Classification according to position of mobile phone in relation to the body into Group C: Trouser pocket; group D: waist pouch; group E: shirt pocket was done. Semen analysis was carried out for all subjects in addition; serum testosterone measurement was done for 100 subjects. The laboratory values of semen parameters significantly differ in all user groups as compared to non user groups. The longer the duration of daily exposure to cell phones, the greater decrease in semen parameters (sperm count, motility and normal morphology). The lower sperm count, motility and normal morphology were in the group B of mobile phone users who used cell phones for 4-6 years duration as compared to group A who used it for 1-3 years. There was no significant difference in mean serum testosterone e level in different mobile user groups. Keeping cell phones in the trouser pocket has been found to decrease sperm count, motility, and normal morphology as compared to men keeping phones in the waist pouch and shirt pocket. The present study conclude that the use of mobile phone decreases the semen quality in study subjects by decreasing count, motility and normal morphology.